2004
DOI: 10.1557/jmr.2004.0372
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition of ruthenium and ruthenium oxide thin films for advanced complementary metal-oxide semiconductor gate electrode applications

Abstract: A low-temperature (320–480 °C) metal-organic chemical vapor deposition (MOCVD) process was developed for the growth of ruthenium and ruthenium oxide thin films. The process used bis(ethylcyclopentadienyl)ruthenium [Ru(C5H4C2H5)2] and oxygen as, respectively, the ruthenium and oxygen sources. Systematic investigations of film formation mechanisms and associated rate limiting factors that control the nucleation and growth of the Ru and RuO2 phases led to the demonstration that the MOCVD process can be smoothly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…The deposition of ruthenium thin films on SiO 2 /Si substrates was controlled by surface reaction kinetics as the rate-limiting step (with an activation energy of 1.4 eV) below 400°C, and by the mass-transport process above 400°C. In spite of the fact that the precursor flow rate in our investigation was several orders of magnitude lower than that reported by Papadatos et al, [16] and by Matsui et al, [17] our growth rate values are comparable with reported ones. This fact confirms the advantages of using the precursor solvent.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The deposition of ruthenium thin films on SiO 2 /Si substrates was controlled by surface reaction kinetics as the rate-limiting step (with an activation energy of 1.4 eV) below 400°C, and by the mass-transport process above 400°C. In spite of the fact that the precursor flow rate in our investigation was several orders of magnitude lower than that reported by Papadatos et al, [16] and by Matsui et al, [17] our growth rate values are comparable with reported ones. This fact confirms the advantages of using the precursor solvent.…”
Section: Discussionsupporting
confidence: 81%
“…Above 400°C, the growth was constant at approximately 5.6 nm min -1 , which indicates a mass-transfer-limited regime, where the impingement rate of reactant species on the substrate surface is the rate-controlling step. Papadatos et al [16] and Matsui et al [17] reported comparable growth-rate values by using Ru(EtCp) 2 as a precursor, but in their investigations precur- ). Nabatame et al [15] observed the same effect by using tetrahydrofuran as precursor solvent.…”
Section: Study Of Reaction Kineticsmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, Ru is a promising material for a gate metal in advanced complementary metal-oxide-semiconductor devices [4] and copper seed layer for direct electroplating of Cu metallization [5][6][7]. Especially, its conducting oxide phase, RuO 2 , is also a promising capacitor electrode material [8]. For all these applications, atomic layer deposition (ALD) is the most suitable thin film deposition technique due to its good conformality, uniformity, and low impurity contents.…”
Section: Introductionmentioning
confidence: 99%
“…During the whole process, the formation of RuO 2 was proposed to be hindered through the complete consumption of the subsurface oxygen. However, more recent report has shown that Ru and RuO 2 was controllably formed by changing the growth conditions, for example, O 2 / (Ar + O 2 ) ratios, for Ru ALD using Ru(EtCp) 2 as a Ru precursor [8]. Meanwhile, Kim et al reported that RuO 2 was not formed by ALD using (dimethylpentadienylethylcyclopentadienyl)Ru under similar growth conditions [13].…”
Section: Introductionmentioning
confidence: 99%